The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1038/bjp.2008.280
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Safety Pharmacology

Abstract: Safety Pharmacology is a rapidly developing discipline that uses the basic principles of pharmacology in a regulatory-driven process to generate data to inform risk/benefit assessment. The aim of Safety Pharmacology is to characterize the pharmacodynamic/pharmacokinetic (PK/PD) relationship of a drug's adverse effects using continuously evolving methodology. Unlike toxicology, Safety Pharmacology includes within its remit a regulatory requirement to predict the risk of rare lethal events. This gives Safety Pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(89 citation statements)
references
References 88 publications
1
88
0
Order By: Relevance
“…-22 - present study showed relatively large variability, which phenomenon has been also reported in unanesthetized, unrestrained rats (Pugsley et al, 2008), so it may be said that the values of respiratory parameters show relatively greater variation under the conditions of non-anesthetization and free mobility, regardless of animal species.…”
Section: Discussionsupporting
confidence: 72%
“…-22 - present study showed relatively large variability, which phenomenon has been also reported in unanesthetized, unrestrained rats (Pugsley et al, 2008), so it may be said that the values of respiratory parameters show relatively greater variation under the conditions of non-anesthetization and free mobility, regardless of animal species.…”
Section: Discussionsupporting
confidence: 72%
“…To date, no studies on the effects of a dopamine D 3 receptor antagonist and cocaine in dogs have appeared. Dogs are a mainstay of cardiovascular safety evaluation of drugs (Pugsley et al, 2008;Ewart et al, 2013). Although it is uncertain whether the interaction between a dopamine D 3 receptor antagonist and cocaine we are reporting in dogs is predictive of a similar effect in humans, this finding would likely preclude further development of such a compound as a treatment for cocaine use disorder.…”
Section: Discussionmentioning
confidence: 94%
“…Exposure of these cultured neurons to a drug candidate can determine at an early stage of preclinical testing whether the drug is toxic to neurons and, for example, initiates apoptosis ). An important aim in drug development is to discover detrimental effects as early as possible (Pugsley et al, 2008). This is of particular importance when testing new antiepileptic drugs that interfere with glutamate (as NMDA antagonists) or GABA signaling, or to discover off-target effects of other potential drugs.…”
Section: Expanding the Use Of The Chicken Embryo Modelmentioning
confidence: 99%
“…Lack of safety contributes to 30% of failures, whereas lack of efficacy is the other major cause of attrition (Kola and Landis, 2004). The fact that several drug candidates progressed well into clinical trials before rare and potentially lethal adverse effects were detected led to an extension of nonclinical trials and the foundation of safety pharmacology as a discipline in the late 1990s (Pugsley et al, 2008). One of the ICH M3 (R2) safety guidelines referenced is S7A, "Safety Pharmacology Studies for Human Pharmaceuticals," (ICH, 2009) which defines a core battery of vital organs for which the impact of new drugs needs to be assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation